Airway Management for Neonates with Beckwith-Wiedemann Syndrome (Bws): Case Report - Darmestari, Dara Lalita (Jurnal Komplikasi Anestesi, 2025)
Introduction: Beckwith-Wiedemann syndrome (BWS) is a congenital disorder with abnormalities such as macroglossia and abdominal wall defect. Children with BWS predicted to have difficult airway due to macroglossia in perioperative airway management. Management : 4 days old male neonates with macroglossia on BWS is schedule for umbilical cord hernia revision. Patient was assessed as ASA 3 based on his physical status. First patient was pre-oxygenated and ventilation using size 1 mask, and after ventilation archived, induction started with 4 vol% Sevoflurane followed by intravenous agent Fentanyl 7.5 mcg and Atracurium. The initial intubation attempt with direct laryngoscope failed due to unclear visualization of vocal cord because obstruction of the tongue. The second attempt was made using VL, vocal folds visualized according to Cormack–Lehane grade IIb, and neonate bougie with a kinking, size 3 uncuffed ETT. Postoperatively, patient was extubated before admitted back to the NICU. Conclusion: Macroglossia causes anatomical airway abnormalities in children with BWS. It was predicted that might cause difficult ventilation, intubation and extubation. Airway management with tongue traction and awake tracheal intubation are reported to facilitate the intubation. Other emergency equipment including bougie, FOB, cricothyroidotomy set, and tracheostomy set needs to be ensured before anesthesia administration begins